A tine to live, a tine to die [large type] - Maxwell, Edith (Maxwell, Edith. Local foods mystery., 2013)
Farmer Cameron Flaherty's first growing season has gotten off to a slow start, but her CSA is flourishing thanks to a group of subscribers led by enthusiastic Brazilian volunteer Lucinda DaSilva. Then Cam fires her only employee because he won't follow organic growing practices. It seems like just another day at the office -- until she finds him with a pitchfork sticking out of his neck. When the police suspect Cam, Lucinda joins her to hunt for the real killer.